399. Multi-centre Observational Study on Epidemiology, Treatment, and Outcome of Mucormycosis in India. (26th November 2018) - Patel, Atul; Kaur, Harsimran; Xess, Immaculata; Michael, Joy S; Savio, Jayanthi; Rudramurthy, Shivaprakash; Singh, Rakesh; Shastri, Prakash; Umabala, Pamidimukkala; Sardana, Raman; Kindo, Anupama Jyoti; Capoor, Malini; et al.
Abstract: Background: Though the rise in number of mucormycosis cases has been reported globally, the rise in India is alarming especially in uncontrolled diabetics. However, multiple gaps exist in the understanding of the disease in this country. Methods: To describe the epidemiology, diagnosis, treatment practices, and outcome of mucormycosis in India. A single-arm prospective observational study was conducted in the network of 17 tertiary care centres across India during April 2016 through September 2017. All consecutive proven mucormycosis patients were enrolled in this study. Clinical data including risk factors, investigations, and treatment were collected. All isolates and histopathological specimens were sent to Mycology Reference Laboratory at Chandigarh for final identification (phenotypic and sequencing) and drug susceptibility testing. Results: A total of 474 cases were enrolled between the study period. Rhino-orbito-cerebral mucormycosis was common (42.7%) presentation with 22.8% patients had brain involvement, followed by pulmonary (14.6%), cutaneous (11.8%), isolated renal (3.9%), and intra-abdominal (2.8%) mucormycosis. The underlying disease or predisposing factors were noted in 79.7% cases (84.9% diabetes mellitus, 12.9% steroids, 10.3% trauma or history of surgery, 9.7% malignancy, and 9.2% transplant). The most common agents isolated were Rhizopus species (75.9%, R. arrhizus [74.3%] and R. homothallicus [6.7%]) followed by Apophysomyces variabilis (7.4%), Mucor species (6%), and Lichtheimia corymbifera (4%). The patients were managed by medical therapy in 82.8%, surgery in 56.8% while 51.7% received combined medical and surgical management. Amphotericin B (96.8%) either lipid formulations (65.7%) or conventional form (39.1%) was the common antifungal used. The mortality of patients was 30.4%; of which, 80.3% patients died within 6 weeks of their diagnosis. 24.3% patients left hospital against medical advice while 50.1% survived. Conclusion: Rhino-orbital-cerebral mucormysosis in uncontrolled diabetics is common presentation in India . R. arrhizus followed by A. variabilis are common species isolated from those patients. Survival was noted only in half of the patients despite increased awareness and diagnosis. Disclosures: All authors: No reported disclosures.